ANALISIS LAPORAN REALISASI ANGGARAN (LRA) PADA DINAS TENAGA KERJA DAN SOSIAL KOTA BALIKPAPAN (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This study aims to determine the level of efficiency in the realization of the Budget Department of Labor and Social Balikpapan. The number of years used for this study three (3) the period starting from the period 2013 to 2015. The period of analysis used Ratios Budget and Expenditure Analysis, Growth Ratio Shopping, Shopping Ratio Operation Against Total Expenditure and Capital Expenditure Ratio Against totall Shopping, Ratio Budget and Expenditure analysis of 2014 an increase of 84.01% compared with the previous year. And in 2015 a decline of 77.00%. The ratio of spending growth in 2015 decreased very significantly by 08:57% compared to 2014 amounting to 37.79 and in the year 2013 by 05:57%. The main cause of this decline is the scope of services of the Department of Labor and Social Balikpapan declining. Operating Expenditure Ratio from 2013 to 2015 the percentage going up and down. Overview Ratios Operating Expenditure in 2013 amounted to 50.10%, while in 2014 an increase of 60.77%. Then in 2015 an increase of 94.31%. The results of the ratio of capital spending began in 2013 amounted to 01.64% increase for the next year is the period of 2014 amounted to 07.61% and down by 2015 amounted to 05.68%. Keywords: Ratio Analysis and Expenditure Budget, Expenditure Growth Ratio, Operating Expenditure Ratio Against Total Expenditure and Capital Expenditure Ratio Against Total Expenditure.